Handset based automatic network re-selection system for GSM/GPRS and WiFi (2008)
This paper presents the results of the development of a handset based automatic network reselection software system, which allows keeping end-to-end connections through semi-transparent handoff on WiFi/GSM-GPRS networks. A description of the developed system's software architecture is given, as well as of the components implemented for it, their functionalities and flow of control, all of which allow the permanent discovery of available networks for the mobile device, their evaluation, selection and switching to the network which offers the best ratings in its performance and operational profile, taking into account the preferences previously configured by the user. The system was developed in Java and C# for different operating systems (WinXP, WinMobile and Linux), and its interoperability has been tested in them. Some of the test scenarios are described and final comments about the tests results are given. Copyright 2008 ACM.